PENGUATAN KARAKTER MELALUI ROLE MODEL WIRACARITA SIJELLO TO MAMPU DENGAN PENDEKATAN PEMBELAJARAN MENDALAM PADA SISWA SEKOLAH DASAR - Lilis Septiani Lista; Andi Srimularahmah; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Muhammad Asdar; A. Nurhabibi Marwil; Sri Wahyuni Putri; A. Milasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an important aspect of elementary education in the era of Society 5.0. However, the Bone Regency Education Report Card, 2023 showed a decline in student discipline, responsibility, and respect, with only 40% of students consistently demonstrating positive character behavior. This study aims to design and implement the Sijello to Mampu Puzzle as an interactive learning medium to strengthen the character values ​​of elementary school students. This study used the R&D method with the ADDIE model. Data were collected using pre-tests, post-tests, questionnaires, interviews, and observation sheets. Quantitative data were analyzed using descriptive statistics and paired t-tests, while qualitative data were analyzed thematically. The results showed that the developed puzzle media achieved a validity score of 87.5% (very valid), a practicality score of 85.2% (very practical), and an effectiveness score of 82.7% (effective).